Microbial patterns in acute exacerbation of chronic obstructive pulmonary disease at tertiary care - Miah, Mohammad Amir Hossain; Mannan, Mohammad Abdul; Ali, Mirza Mohammad Idris; Khan, Mohammad Delwar Jahan; Hoque, A. F. M. Abdul (International Journal of Advances in Medicine, 2024)
Background: In patients experiencing acute exacerbation of chronic obstructive pulmonary disease, infections represent a prevalent cause of mortality. Methods: This study comprised a prospective cohort analysis involving 50 AECOPD patients at a tertiary care hospital located in Cumilla. The sputum culture of these patients was assessed to detect the presence of Gram-positive and Gram-negative microorganisms. Additionally, the sensitivity and resistance patterns of these microorganisms to commonly prescribed antibiotics were investigated. Results: From January 2023 July 2023, sputum cultures of 42% of patients yielded positive results for pathogenic microorganisms. Predominantly, gram-negative organisms such as Klebsiella, Citrobacter, Pseudomonas, and Acinetobacter were isolated. The most prevalent age group among the fifty patients was 61-80 years, constituting 70% of the sample. Subsequently, the age groups of 41-60 years and 81-100 years represented 18% and 12% of the cohort, respectively. Among clinically diagnosed COPD patients experiencing acute exacerbations, 90% were male, with the majority being smokers or exposed to passive smoking. Notably, 26% of patients had a family history of COPD. Furthermore, 97% of patients had a history of respiratory infections, with 20% experiencing upper respiratory tract infections and 80% suffering from lower respiratory tract infections, including acute bronchiolitis, pneumonia, and tracheitis. Conclusions: Klebsiella exhibited relatively high susceptibility to antibiotics such as amoxicillin, azithromycin, ciprofloxacin, and cephalosporins. Conversely, Citrobacter and Pseudomonas displayed diverse susceptibility profiles, showing varying responses to different antibiotics. Additionally, Acinetobacter demonstrated relatively lower susceptibility to several antibiotics tested, suggesting potential challenges in its management.